New Indo-Pacific species of the genus Teretia Norman, 1888 (Gastropoda: Raphitomidae) - Morassi, Mauro; Bonfitto, Antonio (Zootaxa, 2015)
Four new species are assigned to the genus Teretia Norman, 1888 in the family Raphitomidae Bellardi, 1875 and herein described: Teretia neocaledonica sp. nov., T. sysoevi sp. nov., T. tongaensis sp. nov. from the southeastern Pacific and Teretia tavianii sp. nov. from the Gulf of Aden. The new species represent the first Indo-Pacific record of a genus previously known in the recent molluscan fauna by only two species from the Atlantic Ocean-Mediterranean Sea and Southern Africa. A possible Tethyan origin for the genus Teretia is suggested.